Dialectics of development: teacher identity formation in the interplay of ideal ego and ego ideal. Issue 2 (3rd April 2017) - Clarke, Matthew; Michell, Michael; Ellis, Neville John
ABSTRACT: This paper results from research examining pre-service teacher development in relation to experiences of mentoring during the Professional Experience component of their programme. The paper focuses on the interplay between pre-service teachers' personal aspirations for their own practice and identity and their perceptions of more socialized and formalized institutional requirements. The paper highlights the developmental potential of dialectical interactions between these 'inside out' and 'outside in' perspectives on pre-service teachers' practice and identity, drawing on psychoanalytic theory in order to gain insights into this process by viewing the pre-service teachers wishes and aspirations for their practice and identities as manifestations of the Lacanian ('inside out') ideal ego; whilst the school culture and the mentor teachers' (actual and anticipated) comments and judgements are read as representations of the ('outside in') ego ideal. The paper concludes with considerations of how universities and schools, pre-service teachers and mentors, might be encouraged to recognize the need for a sustained and open-ended dialectic between the ego ideal and the ideal ego in ways that might enrich the professional identities available to pre-service teachers.